Challenges in the development of an M4 PAM in vivo tool compound: The discovery of VU0467154 and unexpected DMPK profiles of close analogs. Issue 2 (15th January 2017) - Wood, Michael R.; Noetzel, Meredith J.; Poslusney, Michael S.; Melancon, Bruce J.; Tarr, James C.; Lamsal, Atin; Chang, Sichen; Luscombe, Vincent B.; Weiner, Rebecca L.; Cho, Hyekyung P.; Bubser, Michael; Jones, Carrie K.; et al.
Graphical abstract: Abstract: This letter describes the chemical optimization of a novel series of M4 positive allosteric modulators (PAMs) based on a 5-amino-thieno[2, 3- c ]pyridazine core, developed via iterative parallel synthesis, and culminating in the highly utilized rodent in vivo tool compound, VU0467154 (5 ). This is the first report of the optimization campaign (SAR and DMPK profiling) that led to the discovery of VU0467154, and details all of the challenges faced in allosteric modulator programs (steep SAR, species differences in PAM pharmacology and subtle structural changes affecting CNS penetration).